Cancer cachexia, a clinical challenge. Issue 4 (July 2019) - Argilés, Josep M.; Busquets, Sílvia; López-Soriano, Francisco Javier
Abstract : Purpose of review: The aim of this article is to review the metabolic background of the cachectic syndrome and to analyze the recent therapeutic approaches designed to counteract the wasting suffered by the cancer patient with cachexia. Recent findings: The main changes associated with the development of this multiorganic syndrome are glucose intolerance, fat depletion and muscle protein hypercatabolism. Among the most promising approaches for the treatment of cachexia include the use of ghrelin agonists, beta-blockers, beta-adrenergic agonists, androgen receptor agonists and antimyostatin peptides. The multitargeted approach seems essential in these treatments, which should include the combination of both nutritional support, drugs and a suitable program of physical exercise, in order to ameliorate both anorexia and the metabolic changes associated with cachexia. In addition, another very important aspect for the design of clinical trials for the treatment of cancer cachexia is to staging cancer patients in relation with the degree of cachexia, in order to start as early as possible, this triple approach in the course of the disease, even before weight loss can be detected. Summary: Cancer cachexia has two main components: anorexia and metabolic alterations and both have to be taken into consideration for the treatment of the syndrome.